PERLINDUNGAN HUKUM TERHADAP KREDITUR DALAM PELAKSANAAN EKSEKUSI JAMINAN FIDUSIA DI CIMB NIAGA AUTO FINANCE CABANG MEDAN - HELENA ANGGREANI WIDIAWATI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Dr. Sutiarnoto, SH, Mhum2.  Prof. Dr. Suhaidi, SH, MH3.  Dr. Jelly Leviza, SH, MHum The main problem faced by a financing company which gives credit and financing is the transfer of the collateral to the third party. It is more difficult to handle since the transfer ( through buy and sell, rent, and others) will cause the conflict between the third party as the controller oh the collateral and the creditor as its real owner. The research problems are how about legal implication if debtor transfer collateral to the third party in a financing contract, how about the implemention of the execution on fiduciary collateral by a debtor to the third party,and how about legal protection for CIMB Niaga Auto, Medan Branch, in the implemention of execution on fiduciary collateral which has been transferred by debtor to the third party.Keywords: Execution; Fiduciary Collateral